Hello Reader! Picture Dictionary - Gina Shaw (New York, United States Scholastic US, 1999)
Based on the popular Hello Reader! series of easy-to-read books, this picture dictionary includes more than 500 words. Designed in a reader-friendly layout, each spread features vibrant, multicultural artwork of four favorite Hello Reader! illustrators -- Ron Fritz, Patti Good now, Christina Ong, and Marcy Dunn Ramsey.
Keywords: Read Aloud -- Read Aloud